Effect of Carbon Nanotubes on the Transport and Retention of Bacteria in Saturated Porous Media - Yang, Haiyan; Meiping Tong; Kim, Hyunjung (Environmental Science & Technology, 2013)
This study investigated the influence of carbon nanotubes (CNTs) on the transport and retention behaviors of bacteria (E. coli) in packed porous media at both low and high ionic strength in NaCl and CaCl2 solutions. At low ionic strengths (5 mM NaCl and 0.3 mM CaCl2), both breakthrough curves and retained profiles of bacteria with CNTs (both 5 and 10 mg L-1) were equivalent to those without CNTs, indicating the presence of CNTs did not affect the transport and retention of E. coli at low ionic strengths. The results were supported by those from cell characterization tests (i.e., viability, surface properties, sizes), which showed no significant difference between with and without CNTs. In contrast, breakthrough curves of bacteria with CNTs were lower than those without CNTs at high ionic strengths (25 mM NaCl and 1.2 mM CaCl2), suggesting that the presence of CNTs decreased cell transport at high ionic strengths. The enhanced bacterial deposition in the presence of CNTs was mainly observed at segments near the column inlet, leading to much steeper retained profiles relative to those without CNTs. Additional transport experiments conducted with sand columns predeposited with CNTs revealed that the codeposition of bacteria with CNTs, as well as the deposition of the cell-CNTs cluster formed in cell suspension due to cell bridging effect, largely contributed to the increased deposition of bacteria at high ionic strengths in porous media.